The Effect of Education Through Power Point Media and Infographic Media on Knowledge, Attitude and Action Improvement on Vegetables and Fruits In School Children at Elementary School Sidosermo 1 Surabaya - Nadia Gita Fernanda; Taufiqurrahman; Eny Sayuningsih (Journal of Nutrition Explorations, 2023)
Food is needed by all age groups, including school-age children for the process of growth and development. The results of the 2018 East Java Province Riskesdas showed that the percentage of the age group ≥ 5 years was lacking in vegetable and fruit consumption, namely 93.9%. The purpose of this study was to determine the effect of education through power point media and infographic media about vegetables and fruit for school children at SDN Sidosermo 1 Surabaya. The type of research used is Quasi Experimental with the type of One-Group Pretest Posttest Design. Data collection is done by questionnaire. The number of research samples was 40 people. Statistical test using the Wilcoxon Signed Rank Test. Based on the results of the study, it was obtained that the value of p = 0.00, namely p <a 0.05, which indicates that there is an effect before and after being given education through power point media and infographic media on increasing knowledge, attitudes and actions about vegetables and fruit in class school children 5 at SDN Sidosermo 1 Surabaya.